The Effect Of Tannic Acid Crosslinker On The Properties Of Kenaf Fibre And Polyvinyl Alcohol Binder - Mohammad, Anis Najihah (Universiti Sains Malaysia, 2022)
This research aims to determine the effect of different compositions of PVA (30, 40 wt%) in kenaf on impact strength and water absorption as a binder for kenaf fiber (KF) and to examine the effects of tannic acid as crosslinker on properties of the composite. However, significant moisture absorption and fiber dimensional changes can cause produced composites to swell, and poor interfacial adhesion between the kenaf fiber and PVA matrix led to a reduction in the strength parameters. The composites were prepared by solution blending technique while water absorption percentage, impact strength, morphology using Optical Microscopy (OM) and thermal stability ofthe composites were evaluated using Different Scanning Calorimetry (DSC) and Thermogravimetric analysis (TGA). Stage 1 focuses on the properties of 30 wt % and 40 wt% of PVA in KF/PVA composites. The 70KF/30PVA composites absorbed less water and possessed higher impact strength than 60KF/40PVA. However, the thermal stability and crystallization ability of PVA is reduced in both composites. With the inclusion of 15% and 20% based on PVA of tannic acid (TA) crosslinker, stage 2 70KF/30PVA was selected to further research its properties. The percentage of PVA based on 15% was selected as it showed suitable material's water absorption, impact strength, and thermal analysis capabilities.